Mitochondrial-epigenetic crosstalk as an integrative standpoint into gut microbiome dysbiosis and related diseases - Simão, Vinícius Augusto (2024)
The interplay between mitochondria, epigenetics, and the microbiota is intricately linked to both health and disease. Within our cells, a complex molecular dance occurs, where these components intertwine in a mesmerizing ballet that plays a decisive role in our health. Mitochondria, beyond being energy powerhouses, modulate nuclear gene expression through messengers like reactive oxidative stress (ROS) and calcium. Epigenetics, acting as the molecular conductor, regulates the expression of both nuclear and mitochondrial genes through modifications like DNA methylation. The intestinal microbiota itself produces short-chain fatty acids (SCFAs) that influence mitochondrial activity. SCFA-induced epigenetic modifications, like histone acetylation, impact mitochondrial function which may lead to disease. Mitochondrial dysfunction generates retrograde signals that alter nuclear gene expression, as evidenced by increased histone H3 lysine 27 acetylation (H3K27ac) in genes essential for neuronal differentiation and mitochondrial reprogramming. Alterations in the mitochondrial-nuclear-microbiota axis are associated with diseases including diabetes, neurodegeneration, and cancer. Modulating the intestinal microbiota with probiotics or prebiotics can restore balance while intervening in mitochondrial pathways, which can be a therapeutic strategy. Additionally, using epigenetic agents like histone deacetylase (HDAC) inhibitors can reprogram gene expression and improve mitochondrial function. Finally, the present review aims to explore the central interplay between mitochondria, epigenetics modifications, and microbiota in a complex and dynamic molecular context that plays a fundamental role in human health. Specifically, it will examine the impact of microbiome components and metabolites generated from normobiosis and dysbiosis on mitochondria and epigenetic modifications across different diseases and metabolic conditions. This integrated understanding of the molecular players and their interactions provides a deeper perspective on how to promote health and potentially combat disease.